Pengaruh Lingkungan dan Fasilitas Belajar terhadap Prestasi Belajar Siswa pada Mata Pelajaran IPS - Anissa Kalimatu Sholihah; Nastiti Mufidah (JIIPSI: Jurnal Ilmiah Ilmu Pengetahuan Sosial Indonesia, 2021)
This research is motivated by the number of school institutions that are far from the city center. There are several buildings and learning facilities that are damaged and incomplete. This study aims to (1) determine whether there is a significant influence between the learning environment on student achievement in social studies subject for class VIII at SMPN 1 Sambit Ponorogo. (2) Knowing whether there is a significant influence between learning facilities on student achievement in social studies subject for class VIII at SMPN 1 Sambit Ponorogo. (3) Knowing whether there is a significant influence between the environment and learning facilities on student achievement in social studies subject for class VIII at SMPN 1 Sambit Ponorogo. This study uses a quantitative approach. The research population was all students of class VIII, amounting to 69 students. The sample used is probability sampling technique. The data collection methods were questionnaires, interviews, and documentation. The data analysis technique is simple and multiple linear regression analysis. The results are: (1) there is a significant influence between the learning environment on student achievement with a percentage of 24.1%. (2) there is a significant influence between learning facilities on student achievement with a percentage of 15.9%. (3) there is a significant influence between the learning environment and learning facilities on the learning achievement of students in IPS subject class VIII at SMPN 1 Sambit Ponorogo with a percentage of 29.2%.